2013
DOI: 10.1136/medethics-2012-101077
|View full text |Cite
|
Sign up to set email alerts
|

Participant experience of invasive research in adults with intellectual disability

Abstract: Clinical research is a necessity if effective and safe treatments are to be developed. However, this may well include the need for research that is best described as 'invasive' in that it may be associated with some discomfort or inconvenience. Limitations in the undertaking of invasive research involving people with intellectual disabilities (ID) are perhaps related to anxieties within the academic community and among ethics committees; however, the consequence of this neglect is that innovative treatments sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
1
0
1
Order By: Relevance
“…Although research participation was paired with clinically indicated blood monitoring, many residential home staff declined to facilitate a Best Interests model of substitute decision‐making in the absence of an Independent Mental Capacity Advocate (IMCA). Unwillingness or inability of support workers to facilitate participation of PwID in research involving invasive procedures is common and our study confirms it (McAllister et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…Although research participation was paired with clinically indicated blood monitoring, many residential home staff declined to facilitate a Best Interests model of substitute decision‐making in the absence of an Independent Mental Capacity Advocate (IMCA). Unwillingness or inability of support workers to facilitate participation of PwID in research involving invasive procedures is common and our study confirms it (McAllister et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…John et al, 2022); d) Inaccessible language and documents(St. John et al, 2022); e) Use of offensive or outdated language in research policies and associated documents(St. John et al, 2022); f) Difficulty in recruiting diverse people among the group, which includes the possibility of coercion from caregivers, family members and/or legal guardians(Goldsmith & Skirton, 2015;St. John et al, 2022;Tuffrey-Wijne et al, 2008); g) Difficulty in obtaining consent(McAllister et al, 2013;St. John et al, 2022); h) Systematic exclusion related to participation(St. John et al, 2022); i) Protection of ethics boards(McAllister et al, 2013;Watchman et al, 2019); j) A high probability that it will be necessary to request an extension of time, which implies a restriction on costs(McAllister et al, 2013); k) Possibility of gatekeeping by associations/organizations, caregivers, family members and legal guardians(Tuffrey-Wijne et al, 2008); l) Lack of privacy that PwID may be subject to from caregivers(Hall, 2013); m) Lack of knowledge, on the part of ethics councils, about capabilities, needs, correct "(...) the form itself [ for ethical approval] is a barrier to inclusion (..…”
mentioning
confidence: 99%
“…; g) Dificuldades em obter consentimento(McAllister et al, 2013;St. John et al, 2022); h) Exclusão sistemática relacionada com a participação(St. John et al, 2022);i) Proteção dos conselhos de ética (McAllister et al, 2013; Watchman et al, 2019); j) Grande probabilidade de ser necessário pedir uma extensão de tempo, o que implica uma restrição nos custos (McAllister et al, 2013); k) Possibilidade de haver gatekeeping por parte das associações/organizações, de cuidadores, familiares e responsáveis legais (Tuffrey-Wijne et al, 2008);…”
unclassified